Alohtone biljne vrste u flori i vegetaciji Crnog luga (jugozapadni Srem) - Jarić, Snežana; Vrbničanin, Sava (Acta herbologica, 2019)
The aim of the research was to establish the presence of allochthonous plant species in the Crni lug region and the surrounding area (south-western Srem). Research was undertaken in floodplain, ruderal and segetal habitats during the vegetative season between 2009 and 2014. Of the total number of species recorded (285), 32 taxa were allochthonous plants, which were classified into 19 families. A phytogeographical analysis of their primary distribution area established that the majority fell into the category of ‘adventive’ floral species. The chorological spectrum shows the domination of species of North American origin (57%), while therophytes have the greatest presence in the biological spectrum. Neophytes dominate the chronological spectrum (75%) and analysis of the invasive status revealed the co-dominance of naturalized and invasive allochthonous plant species (47% each). In the study area, most allochthonous species were detected in the foreland of the River Sava and flood protection channels (26), in the Populetum nigrae-albae and Amorpho-Typhaetum ass. nova communities; next to roads and on abandoned land (21), in the Chenopodio-Ambrosietum artemisiifoliae ass. nova community; on cultivated land (18), in the Polygonetum convolvulo-avicularis, Consolido-Polygonetum avicularis and Lolio-Plantaginetum majoris communities; and on the levee and in meadows (14), in the Asclepietum syriacae community. The most common dispersion methods for the allochthonous species in the study area are anthropochory (40.6%) and anemochory (34.4%). Floodwaters, water level and, in part, anthropogenic factors have the most pronounced impact on the presence of species and their dispersal in the foreland of the River Sava and in the flood protection channel zone, while the effects of anthropogenic factors are most intensive in ruderal and segetal areas.